2014
DOI: 10.1128/aac.03831-14
|View full text |Cite
|
Sign up to set email alerts
|

KPC-Producing Klebsiella pneumoniae Strains That Harbor AAC(6′)-Ib Exhibit Intermediate Resistance to Amikacin

Abstract: The aminoglycoside-modifying enzyme AAC(6=)-Ib is common among carbapenem-resistant Klebsiella pneumoniae (CR-Kp) strains. We investigated amikacin (AMK) activity against 20 AAC(6=)-Ib-producing CR-Kp strains. MICs clustered at 16 to 32 g/ml. By the time-kill study, AMK (1؋ and 4؋ the MIC) was bactericidal against 30% and 85% of the strains, respectively. At achievable human serum concentrations, however, the majority of strains showed regrowth, suggesting that AAC(6=)-Ib confers intermediate AMK resistance. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 17 publications
1
8
1
Order By: Relevance
“…22,23 In this study, non-use of steroids was detected as a protective factor in terms of CRKP development (Odds ratio: 0.244; %95; CI: 0.072-0.822; p < 0.05). However, in contrast to our study, Bremmer et al 24 demonstrated that systemic steroids use is not a risk factor for CRKP development. It has been thought that different results may arise from the selection of the patient population.…”
Section: Discussioncontrasting
confidence: 99%
“…22,23 In this study, non-use of steroids was detected as a protective factor in terms of CRKP development (Odds ratio: 0.244; %95; CI: 0.072-0.822; p < 0.05). However, in contrast to our study, Bremmer et al 24 demonstrated that systemic steroids use is not a risk factor for CRKP development. It has been thought that different results may arise from the selection of the patient population.…”
Section: Discussioncontrasting
confidence: 99%
“…The next-generation aminoglycoside plazomicin has been evaluated in two phase 3 clinical studies in patients with complicated urinary tract infections (cUTI) or acute pyelonephritis (AP) and in patients with bloodstream infections, hospital- and ventilator-associated bacterial pneumonia, or cUTI/AP due to CRE. Aminoglycosides are often used to treat CRE, as these drugs are bactericidal against these strains; however, increasing resistance due to the presence of genes encoding aminoglycoside-modifying enzymes (AMEs) has given clinicians pause ( 6 8 ), as these organisms typically carry multiple resistance determinants ( 9 , 10 ). Plazomicin maintains activity against most aminoglycoside-resistant Enterobacteriaceae as it is not inactivated by plasmid-borne AMEs ( 11 ).…”
Section: Textmentioning
confidence: 99%
“…High in vitro efficacy of amikacin has been observed in other studies (13) (16) and has been attributed to the limited clinical use of aminoglycosides over the last decades (23) . However, its higher MIC for carbapenemresistant isolates suggests that these isolates are intermediately resistant to amikacin (24) .…”
Section: Ethical Considerationsmentioning
confidence: 99%